A case study analysis of extension service provision in Malawi - Lamm, Kevan W.; Masambuka-Kanchewa, Fallys; Lamm, Alexa J.; Davis, Kristin E.; Nahdy, Silim; Oyugi, Millicent A. (Academic Journals, 2021)
Evidence suggests that a lack of extension agents impedes the effective delivery of agricultural extension services in Malawi and many other developing nations. The purpose of this study was to examine the initiatives taken by the Malawi Forum for Agricultural Advisory Services Delivery (MaFAAS) to address the extension shortage. The research questions were addressed using a qualitative case study approach. MaFAAS and other partners launched an initiative to teach youth from local communities, particularly in rural regions, in agricultural extension so that they can serve their communities in positions comparable to extension agents. The effort resulted in the hiring of 427 extension agents to serve in their areas. While recruiting extension agents alone will not address the problem immediately, it is a start. The beneficial consequences of the Malawian organizations' partnership give an opportunity and potential paradigm for addressing the extension shortfall and difficulties farmers confront in Malawi and beyond.